Effects of EPA and DHA on blood pressure and inflammatory factors: a meta-analysis of randomized controlled trials - Guo, Xiao-fei; Li, Ke-lei; Li, Jiao-mei; Li, Duo (Critical reviews in food science and nutrition, 2019)
The present study aimed to clarify whether eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) have differential effects on blood pressure and inflammatory mediators. A systematic literature search was conducted in PubMed and Scopus updated to Apr. 2018. The mean changes in risk factors of chronic diseases were calculated as weighted mean difference (WMD) by using a random-effects model. Twenty randomized controlled trials (RCTs) were included. The summary estimate showed that EPA intervention significantly reduced systolic blood pressure (SBP) (-2.6 mmHg; 95%confident interval (CI): -4.6, -0.5 mmHg), especially in subjects with dyslipidemia (-3.8 mmHg; 95%CI: -6.7, -0.8 mmHg). The pooled effect indicated that supplemental DHA exerted a significant reduction in diastolic blood pressure (DBP) in subjects with dyslipidemia (-3.1 mmHg; 95%CI: -5.9, -0.2 mmHg). Both EPA (-0.56 mg/L; 95%CI: -1.13, 0.00) and DHA (-0.5 mg/L; 95%CI: -1.0, -0.03) significantly reduced the concentrations of C-reactive protein (CRP), respectively, especially in subjects with dyslipidemia and higher baseline CRP concentrations. Given that limited trials have focused on EPA or DHA intervention on concentrations of interleukin (IL)-6 and tumor necrosis factor (TNF)-α, further RCTs should be explored on these inflammatory factors. The present meta-analysis provides substantial evidence that EPA and DHA have independent (blood pressure) and shared (CRP concentration) effects on risk factors of chronic diseases, and high-quality RCTs with multi-center and large simple-size should be performed to confirm the present findings.